The Ukrainian Crisis - An Unpredictable Event? - Ana Maria Costea (CES Working Papers, 2016)
For years Ukraine tried to balance between the EU and Russia. The strategy proved to be inefficient due to the fact that Ukraine did not hold the required leverage for this kind of strategy and the consequence was observed in the current instability from the Ukrainian state. At the same time, these events are the effect of an announced Russia's change of strategy. Crimea's annexation and the violent acts from Donbas put under question mark the security and stability of the entire European continent. The EU's legitimacy vis-à-vis its global power status given its inability to act regionally in an efficient manner. Additionally, Russia was perceived as a revisionist state that did not follow the international rules anymore. To a certain point the events from Ukraine were viewed as a new type of war in terms of tactics. The present article aims to analyse the degree to which the events from Ukraine were predictable. The main research question of the study revolves around the following: Taking into account Russia's perceptions over itself, Ukraine and the EU, was the Ukrainian crisis a predictable event? Regarding the methodology, the article will concentrate on document analysis (primary and secondary sources), in order to emphasize the correlation between the different/similar meanings that are displayed within the strategic, official documents and the discourse level, to see if there were some hints regarding the events that were to be developed.
Keywords: F51; 330; EU; perceptions; predictability; Russia; Ukraine